2022
DOI: 10.3389/fnut.2022.1034743
|View full text |Cite
|
Sign up to set email alerts
|

Dietary ketosis improves circadian dysfunction as well as motor symptoms in the BACHD mouse model of Huntington’s disease

Abstract: Disturbances in sleep/wake cycles are common among patients with neurodegenerative diseases including Huntington’s disease (HD) and represent an appealing target for chrono-nutrition-based interventions. In the present work, we sought to determine whether a low-carbohydrate, high-fat diet would ameliorate the symptoms and delay disease progression in the BACHD mouse model of HD. Adult WT and BACHD male mice were fed a normal or a ketogenic diet (KD) for 3 months. The KD evoked a robust rhythm in serum levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…The mechanisms underlying these benefits of TRF on central nervous system function are not known although there are several possibilities (Longo and Panda, 2016; Jensen et al, 2020; Bass, 2024). In recent work, we reported that a ketogenic diet (KD) ameliorates the symptoms and delays disease progression in the BACHD model (Whittaker et al, 2022). Mutant mice fed a KD for three months displayed increased daytime sleep and improved timing of sleep onset.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying these benefits of TRF on central nervous system function are not known although there are several possibilities (Longo and Panda, 2016; Jensen et al, 2020; Bass, 2024). In recent work, we reported that a ketogenic diet (KD) ameliorates the symptoms and delays disease progression in the BACHD model (Whittaker et al, 2022). Mutant mice fed a KD for three months displayed increased daytime sleep and improved timing of sleep onset.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study showed that peripheral clocks were also dysregulated [32]. At a molecular level, alterations in the amplitude or phase of the rhythms in core circadian clock gene expression were seen in several brain regions beyond the SCN, including striatum, hippocampus, and motor cortex [19] and peripheral tissues, particularly the liver [32,33]. Notably, pathophysiology is also described in HD mouse SCN [34].…”
Section: Micementioning
confidence: 97%
“…Mice on this restricted feeding regime showed improvements in their locomotor activity and sleep behavioral rhythms and heart rate variability, with motor improvements correlated with improved circadian output. The mechanisms underlying these benefits of time restricted feeding are not known, although improvements in metabolism that occur in HD would seem to be a logical line of investigation, since metabolism is dysregulated in HD models [32,33,45,54].…”
Section: Scheduled Feedingmentioning
confidence: 99%
“…32,34 Of note, preclinical studies have found KD treatment also improves sleep and sleep architecture in models of Alzheimer’s disease and Huntington’s disease. 35,36…”
Section: Comorbiditiesmentioning
confidence: 99%
“…32,34 Of note, preclinical studies have found KD treatment also improves sleep and sleep architecture in models of Alzheimer's disease and Huntington's disease. 35,36 Cognitive Deficits Preclinical treatment with KD improves cognitive processes in epilepsy models. In vivo, preclinical experiments assess memory acquisition by measuring how quickly and efficiently a task is learned.…”
Section: Sleep Disordersmentioning
confidence: 99%